Frontotemporal Dementias. Issue 2 (April 2016) - Finger, Elizabeth C.
Abstract : Purpose of Review: : This article reviews the common behavioral and cognitive features of frontotemporal dementia (FTD) and related disorders as well as the distinguishing clinical, genetic, and pathologic features of the most common subtypes. Recent Findings: : Advances in clinical phenotyping, genetics, and biomarkers have enabled improved predictions of the specific underlying molecular pathology associated with different presentations of FTD. Evaluation of large international cohorts has led to recent refinements in diagnostic criteria for several of the FTD subtypes. Summary: : The FTDs are a group of neurodegenerative disorders featuring progressive deterioration of behavior or language and associated pathology in the frontal or temporal lobes. Based on anatomic, genetic, and neuropathologic categorizations, the six clinical subtypes of FTD or related disorders are: (1) behavioral variant of FTD, (2) semantic variant primary progressive aphasia, (3) nonfluent agrammatic variant primary progressive aphasia, (4) corticobasal syndrome, (5) progressive supranuclear palsy, and (6) FTD associated with motor neuron disease. Recognition and accurate diagnoses of FTD subtypes will aid the neurologist in the management of patients with FTD.